Role of Diffusion-Weighted Echo-Planar MR Imaging in Differentiation of Residual or Recurrent Head and Neck Tumors and Posttreatment Changes - Razek, A.A.K. Abdel; Kandeel, A.Y.; Soliman, N.; El-shenshawy, H.M.; Kamel, Y.; Nada, N.; Denewar, A. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: The purpose of this work was to evaluate whether diffusion-weighted MR imaging can be used in differentiating residual or recurrent head and neck tumors from postoperative or postradiation changes.MATERIALS AND METHODS: This study included 32 patients clinically suspected for recurrent head and neck tumor after surgery (n=3), radiation therapy (n=13), or both (n=16). Diffusion-weighted MR imaging was done by using a single-shot spin-echo echo-planar sequence. The apparent diffusion coefficient (ADC) value of the suspected lesion was calculated and correlated with pathologic results.RESULTS: Adequate diffusion-weighted MR images and ADC maps were obtained in 30 patients (93.8%). The mean ADC value of residual or recurrent lesions (1.17 ± 0.33 × 10−3 mm2/s) was less than that of posttherapeutic changes (2.07 ± 0.25 × 10−3 mm2/s), and the difference was statistically significant (P < .001). When an ADC value of 1.30 × 10−3 mm2/s was used as a threshold value for differentiation, the best results were obtained with an accuracy of 87%, sensitivity of 84%, specificity of 90%, positive predictive value of 94%, and negative predictive value of 76%.CONCLUSIONS: Diffusion-weighted MR imaging with ADC measurement has promising results for differentiating residual or recurrent head and neck tumors from postoperative or postradiation changes.